An unusual presentation revealing pancreatic carcinoma: Sister Mary Joseph Nodule - Hafi da Sghir; Soumia Jellal; Adil Ait Errami; Sofi a Oubaha; Zouhour Samlani; Khadija Krati (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2019)
Sister Mary Joseph Nodule (SMJN) is a cutaneous nodule resulting from metastasis of malignant tumors affecting the umbilicus; it had been reported in 0.7e10.4% of patients. This case report describes an 82-year-old male diagnosed with metastatic pancreatic adenocarcinoma and confi rmed by the biopsy of Sister Mary Joseph's nodule.